Manejo integrado del mildiu (Phytophthora infestans L.) en el cultivo de tomate (Solanum lycopersicum L.) - Murillo Cantos, Carlos Isaac (2024)
The tomato (Solanum lycopersicum) is a vegetable of great economic and dietary importance, especially in Ecuador. However, its production faces threats such as mildew, caused by the fungus Phytophthora infestans. This disease affects the aerial part of the plant at any stage, spreading in conditions of humidity and low temperatures. Integrated management of mildew in tomatoes is essential, combining cultural strategies and preventive treatments with fungicides. Genetic diversification with resistant varieties and early detection are key. The lack of agricultural information and training in Ecuador is a challenge. The research aims to characterize integrated management of mildew, describing symptoms, damages, and necessary agricultural practices. This includes cultural strategies, biological, chemical, and physical methods. Regular surveillance is essential for effective intervention. Responsible use of chemicals is crucial, considering their environmental and health impact. Selection of resistant varieties and a holistic, sustainable approach are fundamental. Crop rotation, resistant varieties, and monitoring programs are recommended to improve integrated management of mildew in tomatoes.